STUDY OF WHEAT ROOT ROTS ON DIFFERENT VARIETIES AND IMPROVEMENT OF CONTROL MEASURES (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
The article presents the results of studies on the distribution and harmfulness of root rot diseases of winter wheat under the conditions of the Pskent and Kuyichirchik districts of the Tashkent region. Field experiments were conducted in the farms “Otabek Shahlo” and “Yangi Hayot”, where the resistance of wheat varieties “Grom” and “Alekseich” to root rot pathogens (Fusarium spp., Bipolaris sorokiniana) was studied, and the effectiveness of modern seed treatment fungicides — Vaybrans Integral and Maksim Forte — was evaluated. Based on the obtained data, practical recommendations were developed to improve the wheat protection system against root rots under regional conditions.
Keywords: Wheat, root rot, Fusarium, Bipolaris, fungicide, yield.